Giving voice to children in research: The power of child-centered constructivist grounded theory methodology - Sudarsan I; Hoare K; Sheridan N; Roberts J (Wiley Periodicals LLC, 2022)
There has been a growing interest in giving voice to children in response to the introduction of the United Nations Convention on the Rights of the Child and evolving sociological discourses on childhood. Using child-sensitive methodologies such as constructivist grounded theory (CGT) enables children's voices to contribute authentic, meaningful, and eventually more actionable data, capable of informing policies and practices in children's best interests. In this article, we discuss how researchers using CGT can privilege children's voices through effective knowledge coconstruction by creating a child-sensitive research space and using methods that are appropriate to their abilities and interests. We draw on selected data from the first author's (I. S.) PhD project that explores Indian immigrant children's and their family carers' beliefs, practices, and experiences of asthma in New Zealand. We encourage researchers to consider CGT as one of the appropriate methodological choices to explicitly promote the voice of the child.
© 2022 The Authors
Keywords: asthma; child-sensitive methods; children's voices; grounded theory; social constructionism; Caregivers; Child; Family; Grounded Theory; Humans; New Zealand; Research Design; 1110 Nursing; 1117 Public Health and Health Services